Secondary students’ spatial thinking in solving the minimum competency assessment (MCA) on geometry - Mayang Dintarini; Anis Farida Jamil; Agung Deddiliawan Ismail (Jurnal Elemen, 2022)
Reflecting on PISA and TIMSS, international mathematical, reading, and science literacy assessments, the Indonesian government began implementing the Minimum Competency Assessment (MCA) for primary, secondary, and high school students. MCA demands the ability to solve daily life problems, one of which is geometry problems that require spatial ability. This research focused on describing spatial thinking ability used in numeracy competencies on geometry content. This research is descriptive with a qualitative approach. Thirty junior high school students in Malang, East Java, Indonesia, took the MCA preparation test and assessed their spatial thinking skills. The research was conducted in three stages: preparation, implementation, and analysis, and showed that three aspects of spatial ability, namely visualization, orientation, and relations, had not yet fully emerged. Some students cannot arrange the expected pattern. There are even students who ignore the geometric shapes requested. Students simplify drawing a hexagon with a quadrilateral, which are two different geometric objects, which leads to fatal errors. This study suggests that teachers emphasize learning mathematics that can train students' spatial thinking skills because it can lead to better mathematical understanding and performance.